Impact of vaccination programs on the incidence of meningococcal infections - Baoum, Shada Omar; Alomar, Yazeed Abdullah; Nedhal Hussein, Mohammed; Alqadeeb, Abdulmohsen Saad; Alzaid, Walid Saad; Aldossari, Abdulmohsin Saria; Alomar, Muhannad Abdullah; Alalwan, Faisal Ameer; Alalwan, Yara Ameer (International Journal Of Community Medicine And Public Health, 2024)
Meningococcal infections, caused by Neisseria meningitidis, are a major cause of morbidity and mortality worldwide, particularly among young children, adolescents, and immunocompromised individuals. Vaccination programs have been instrumental in reducing the incidence of meningococcal disease by targeting the most common serogroups responsible for infections, including A, B, C, W, and Y. The introduction of conjugate and quadrivalent vaccines has resulted in significant declines in infection rates across various regions, demonstrating both direct protection for vaccinated individuals and the establishment of herd immunity, which benefits the entire population by reducing transmission. In mass gatherings, such as the annual Hajj pilgrimage, the risk of meningococcal disease outbreaks is high due to the large influx of people from diverse geographical locations. Mandatory vaccination policies have been implemented to prevent such outbreaks, particularly with quadrivalent vaccines that target the most prevalent serogroups. This has proven highly effective in preventing the spread of meningococcal disease both during and after these events. However, challenges remain in achieving global vaccination coverage, particularly in low- and middle-income countries where healthcare infrastructure and vaccine affordability can be limiting factors. Additionally, vaccine hesitancy driven by cultural and social factors continues to impede vaccination efforts in some regions. Addressing these challenges through enhanced public health campaigns, financial support for vaccination programs, and targeted strategies such as school-based vaccination initiatives is critical to increasing coverage. As meningococcal vaccination programs continue to evolve, ongoing surveillance, public education, and global collaboration will be necessary to sustain progress in controlling this potentially devastating disease. The impact of vaccination extends beyond individual protection, offering community-wide benefits and significantly reducing the global burden of meningococcal infections.